Case Report: Genomic insights into prostate adenocarcinoma transdifferentiation to carcinosarcoma due to lineage plasticity - Fukui, Tomohiro; Fukunaga, Arinobu; Teramoto, Yuki; Fujiwara, Maki; Hikami, Kensuke; Sunada, Takuro; Mizuno, Kei; Kita, Yuki; Sumiyoshi, Takayuki; Goto, Takayuki; Saito, Ryoichi; Kobayashi, Takashi; et al. (Frontiers in Oncology, 2025)
In prostate cancer, it is recognized that adenocarcinoma can transdifferentiate into neuroendocrine prostate cancer (NEPC) owing to lineage plasticity; however, transdifferentiation into other histological types remains uncertain. We present a case of a patient who underwent surgery for adenocarcinoma, which later recurred as prostate carcinosarcoma. Genomic analysis revealed a TMPRSS2-ERG fusion, confirming a common clonal origin and transdifferentiation from adenocarcinoma to carcinosarcoma. Additionally, we identified a frameshift mutation in TP53 and the loss of PTEN and RB1. Transcriptome analysis revealed enriched epithelial-mesenchymal transition and immune-related pathways, a pattern distinct from both adenocarcinoma and NEPC. To our knowledge, this is the first report that comprehensively evaluated the clonal origin of the rare prostate carcinosarcoma and characterized it using genomic and transcriptomic sequencing. It enhances our understanding of prostate cancer lineage plasticity and highlights the importance of developing novel therapies specifically targeted at prostate carcinosarcoma.